Bank stability and toe erosion model as a decision tool for gully bank stabilization in sub humid Ethiopian highlands - Zegeye, Assefa D.; Langendoen, E.J.; Steenhuis, T. S.; Mekuria, Wolde; Tilahun, Seifu A. (Elsevier, 2020)
Gullies that are expanding at alarming rate are responsible for the majority of soil losses in the (sub) humid highlands of Ethiopia. Few affordable and effective methods for gully erosion control are available in the highlands. The objective of the study was to develop cost-effective measures to halt gully expansion by determining stable-bank conditions under a variety of environmental situations using the Bank Stability and Toe Erosion Model (BSTEM). The study was carried out in the sub humid Debre Mawi watershed, located 30 km south of Lake Tana. Input data for the BSTEM model were collected using field surveys and soil sampling. After the BSTEM was tested on actual measured soil data, soil cohesion and internal friction angle were calibrated against observed gully bank retreat. Using the calibrated parameters, the model evaluated the stabilization of the existing gully bank under different scenarios in which groundwater table, bank angle and bank height, tension crack depth, vegetation, and toe protection were varied. Finally, the head-cut of the study gully was treated based on the model recommendation. The simulated results showed that a 5 m deep gully was stable under fully saturated conditions when the bank toe is protected, its upper surface is vegetated, and its bank angles do not exceed 45°. If the depth of the gully is less than 5 m or if its water table is deeper than 0.5 m, only regrading the gully bank to an angle of 45° can stabilize the gully. BSTEM showed to be an effective tool that can be used to evaluate gully control measures.